Youth-Led Social Movements and Peacebuilding in Africa - Bangura, Ibrahim (Routledge Studies in Peace, Conflict and Security in Africa, 2022)
This book critically examines and analyses the active role played by youth-led social movements in pushing for change and promoting peacebuilding in Africa, and their long-term impacts on society. Africa's history is characterised by youth movements. The continent's youth populations played pivotal roles in the campaign against colonialism and, ever since independence, Africa's youth have been at the center of social mobilisation. Most recently, social media has contributed significantly to a further rise in youth-led social movements. However, the impact of youth voices is often marginalised by patriarchal and gerontocratic approaches to governance, denying them the place, voice, and recognition that they deserve. Drawing on empirical evidence from across the continent, this book analyses the drivers and long-term impacts of youth-led social movements on politics in African societies, especially in the area of peacebuilding. The book draws attention to the innovative ways in which young people continue to seek to re-engineer social space and challenge contexts that deny them their voice, place, recognition and identity. This book will be of interest to researchers across the fields of social movement studies, youth studies, peace and conflict studies, history, political sciences, social justice, and African studies.